Collaborative Governance Dalam Pengembangan Kawasan Perbatasan di Pos Lintas Batas Negara Aruk - Sabam, Hiskia; Tahir , Irwan; Dione , Frans (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2026)
The development of border areas constitutes a strategic national agenda that requires the involvement of multiple actors across different levels of government. The Aruk State Border Post (Pos Lintas Batas Negara/PLBN Aruk) functions not only as a symbol of state sovereignty but also as a potential driver of economic and social development for border communities. This study aims to analyze the implementation of collaborative governance in the development of the border area at PLBN Aruk and to identify the supporting and constraining factors affecting inter-agency collaboration. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving central and local government institutions, vertical agencies, and local communities. The findings reveal that collaboration has been formally established through inter-agency coordination forums; however, it remains largely administrative and has not yet evolved into substantive joint decision-making. Power asymmetries, regulatory fragmentation, and the limited meta-governance role of BNPP contribute to a functional implementation gap and partial institutionalization. This study concludes that governance at PLBN Aruk is in a transitional phase toward adaptive multilevel collaborative governance, which requires institutional strengthening, facilitative leadership, and integrated funding mechanisms to ensure sustainable border area development.